Entrepreneurship Education Based on Islamic Work Ethic: Educational Management Review - Supriyanto, Supriyanto; Ghazali, M. Bahri; Yanti, Fitri; Fauzi, Fauzi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand entrepreneurship education by implementing an Islamic work ethic in the patchwork community in Pringsewu Regency. This research was conducted on the community of patchwork craftsmen in Pekon Sukamulya, Banyumas sub-district, Pringsewu Regency from 2019 to 2021 with a qualitative approach type of research was phenomenological. Data can be obtained using observation and interviews, and documentation. Researchers used data analysis techniques starting from preparing units, data categorization, and data interpretation. The results showed that Islamic work ethic-based entrepreneurship education carried out by the patchwork community in Pringsewu Regency in order to improve social welfare was carried out through; maintaining the quality of the products produced, setting prices that are adjusted to market analysis, carrying out promotions, providing exemplary service to customers. This research has implications for the importance of implementing management and educational values in every organizational activity carried out to be able to provide maximum results according to the expectations of all parties.